2020
DOI: 10.1055/a-1082-1080
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Circulating MANF in Women with PCOS is Elevated by Metformin Therapy and is Inversely Correlated with Insulin Resistance and Hyperandrogenism

Abstract: Mesencephalic astrocyte-derived neurotrophic factor (MANF) is a novel neurotrophic factor. Although recent studies have suggested that MANF appeared to be associated with insulin resistance, the results have been inconsistent. The aim of our study was to determine the serum MANF levels in women with PCOS and controls, to investigate their relationship to insulin resistance, and to evaluate circulating MANF changes with metformin intervention in PCOS women. We conducted a series of cross-sectional and intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…However, the expression of MANF is inconsistent in human disease, and studies have shown that circulating serum MANF levels are significantly elevated in patients with primary diabetes and early diabetes with abnormal glucose tolerance (22). In another PCOS-related study, it was noted that the circulating serum MANF level of the PCOS population was significantly lower than that of the control group (23). In our study, a trend toward significantly lower circulating MANF levels was found in the AGHD population.…”
Section: Discussionsupporting
confidence: 52%
“…However, the expression of MANF is inconsistent in human disease, and studies have shown that circulating serum MANF levels are significantly elevated in patients with primary diabetes and early diabetes with abnormal glucose tolerance (22). In another PCOS-related study, it was noted that the circulating serum MANF level of the PCOS population was significantly lower than that of the control group (23). In our study, a trend toward significantly lower circulating MANF levels was found in the AGHD population.…”
Section: Discussionsupporting
confidence: 52%
“…Effect of MANF on glucose homeostasis Impaired glucose homeostasis is often caused by decreased insulin sensitivity in multiple tissues and/or insufficient insulin secretion in dysfunctional pancreatic β cells. We and others found a correlation between circulating MANF level and insulin resistance in patients with prediabetes and T2DM [17,37] (Table 1). In addition to clinical observations, the role of MANF in modulating insulin sensitivity has been studied in various mouse models.…”
Section: Manf In Metabolism Regulationmentioning
confidence: 58%
“…This finding is consistent with other studies showing that decreased serum MANF resulted in the decline of alleviating ER stress. 23,31 Our data suggest that early detection of MANF following TIA have a potential role in improving the immediate risk stratification of patients. This in turn may lead to the development of new pharmacological treatment and more aggressive Table 1.…”
Section: And Heartmentioning
confidence: 81%